Modeling academic leadership in secondary schools: evidence from northeastern Thailand - Dusadee Butburee; Nawee Udorn; Paitoon Puangyod (Institute of Advanced Engineering and Science, 2026)
This study aimed to develop and empirically test a structural equation model of academic leadership among secondary school administrators in northeastern Thailand. Data were collected from 480 administrators using a structured questionnaire and analyzed through confirmatory factor analysis (CFA) and structural equation modeling (SEM). The results indicate that leadership personality and organizational context significantly influence curriculum leadership and innovation culture, which subsequently shape academic leadership outcomes. The proposed model explains 73.8% of the variance in academic leadership, demonstrating strong explanatory power. These findings contribute to the literature by providing an integrated structural framework that highlights the interplay between leadership capacity and contextual support in enhancing instructional quality and school effectiveness. However, the findings should be interpreted with caution due to the cross-sectional design and reliance on self-reported data.